Making it green: the food packaging perceptions and practices of young consumers / Norsyamira Shahrin ... [et al.] - Norsyamira, Shahrin; Rabiatul Adawiyah, Abd Rahman; Noorliza, Zainol; Noor Saliza, Salmi; Mohd Faisal, Abdul Wahab (Universiti Teknologi MARA, Perak, 2016)
Food handler still fails to play their part even when the government imposes “No Plastic Bag” campaign and a ban on polystyrene foam to pack foods. This research focuses on eco-friendly food packaging based on the perception and practice of young consumers, especially the undergraduates of Mara University of Technology Penang Campus (UiTMPP). Questionnaire was constructed and distributed to 315 respondents. The collected data were analyzed with simple descriptive statistic of frequency, mean and standard deviation. Most of the respondents are aware on eco-friendlyfood packaging. They agreed that the university should propose some alternative to control and reduce non-biodegradable foods packaging.